Reliability and validity of Champion's Health Belief Model Scale for breast cancer screening among Malaysian women. - Parisa , Parsa; Kandiah, Mirnalini; Mohd Taib, Mohd Nasir; Abdul Rahman, Hejar; Mohd Zulkefli, Nor Afiah (Singapore Medical Association, 2008)
Introduction: Breast cancer is the leading cause of cancer deaths in Malaysian women, and the use of breast self-examination (BSE), clinical breast examination (CBE) and mammography remain low in Malaysia. Therefore, there is a need to develop a valid and reliable tool to measure the beliefs that influence breast cancer screening practices. The Champion's Health Belief Model Scale (CHBMS) is a valid and reliable tool to measure beliefs about breast cancer and screening methods in the Western culture. The purpose of this study was to translate the use of CHBMS into the Malaysian context and validate the scale among Malaysian women.